COMMERCIAL STRATEGIES FOR THE FUMIGATION SERVICE - Emanuel Acosta Ortiz, Claudio; Lorena Ramírez Duarte, Heidy; Magdalena Jiménez Toledo, María (Revista Gênero e Interdisciplinaridade, 2023)
umigation also contributes to the development of trade, but currently there are very few companies interested in developing this type of activity, mainly due to the high marketing budget it requires and the lack of techniques or technologies to achieve good performance. With the research work, commercial strategies were established for the fumigation service in Ciudad del Este. As a general objective, the description of new strategies to enhance the fumigation service was proposed. To carry out the research work, the quantitative paradigm was used, the method was deductive and the descriptive level. The data collection technique was a survey with closed questions, carried out to companies in the field of fumigation in Ciudad del Este. According to the results obtained from the questionnaire, it was possible to understand that the most current means to promote the fumigation service by companies is customer service and after-sales, they also apply online sales and the vast majority have advice. of marketing, but still require a constant change in their strategies to expand the fumigation service in Ciudad Del Este.